A 3D photothermal bar for efficient steam generation. Issue 1 (February 2023) - Chen, Yuying; Yang, Jixiang; Guo, Jinsong; Fang, Fang
Abstract: Solar water evaporation is a potential technique for clean water production with zero energy input but is restricted by low evaporation rates that are usually below 5 kg m −2 h −1 . We developed a 3D hydrogel using low-price industrial carbon nanotubes and polyacrylamide (3D CAH). The hydrogel was applied as an evaporation layer. Moreover, the hydrogel covered a cotton bar that was used as a water supply layer. In addition, a downwards water supply mode was applied. It is demonstrated that an evaporation rate for a single 3D CAH was as high as 72.3 kg m −2 h −1 . When a number of 3D CAHs worked simultaneously, the 3D CAHs were densely arranged, which resulted in an evaporation rate of 12.2 kg m −2 h −1 . The two evaporation rates were higher than other reported evaporation rates, showing the importance of properly designing the structure of hydrogels. Furthermore, the 3D CAH showed a good performance in anti-salt accumulation. As a result, the 3D CAH is a good candidate for clean water production, considering its high evaporation rate and cost-effectiveness as well as facile fabrication. Highlights: A novel evaporator is developed for efficient water evaporation. Energy input was from ambient temperature and no sunlight is required. An ultrahigh evaporation rate over 70 kg m −2 h −1 is realized. The production cost is low and no salt accumulation is observed.